2017
DOI: 10.1177/0971721817724317
|View full text |Cite
|
Sign up to set email alerts
|

A Methodology for Searching and Allocating Enterprises in the Supply Chain by Using the Business Information Database and Trademark Rights Database

Abstract: As a number of support programmes for competence improvement are provided to small and medium enterprises (SMEs) in Korea, it is recommended that these enterprises collaborate with each other. However, without information about other enterprises in the industry that they belong to or are planning to enter, many SMEs f ind it diff icult to look for partners that they can collaborate with. This article focuses on extracting a list of enterprises in a supply chain of a specif ic industry through a business inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Comprehensively, a lot of studies received the research result of positive effects of manufacturers' external knowledge management in supply chain network on organizational learning capability. Cheng et al (2016) also indicated that the effects of manufacturers' external supply chain integration on operation performance and organizational learning capability could be applied to deal with manufacturers in multinational manufacturers (Flynn, Huo, & Zhao, 2010;Lim et al, 2017;Wong et al, 2011). In this case, the following hypotheses are proposed in this study.…”
Section: Relationship Analysis Of Manufacturers' Knowledge Managementmentioning
confidence: 93%
See 1 more Smart Citation
“…Comprehensively, a lot of studies received the research result of positive effects of manufacturers' external knowledge management in supply chain network on organizational learning capability. Cheng et al (2016) also indicated that the effects of manufacturers' external supply chain integration on operation performance and organizational learning capability could be applied to deal with manufacturers in multinational manufacturers (Flynn, Huo, & Zhao, 2010;Lim et al, 2017;Wong et al, 2011). In this case, the following hypotheses are proposed in this study.…”
Section: Relationship Analysis Of Manufacturers' Knowledge Managementmentioning
confidence: 93%
“…From the aspect of external network integration, a manufacturer needs to coordinate and manage the knowledge of other manufacturers of the same multinational manufacturers as well as acquire, share, and consolidate strategic knowledge and information with external partners (i.e. supply chain partners, mainly suppliers and customers) (Cheng et al, 2016;Lim, Moon, Kim, & Lee, 2017;Swink, Narasimhan, & Wang, 2007).…”
Section: Relationship Analysis Of Manufacturers' Knowledge Managementmentioning
confidence: 99%
“…The former cares mainly about codification and precedent, the latter about rationale and outcome. The one forum in which trademarks are visible––perhaps predictably––is the use of trademark data for computational metrification and landscaping of innovation, most squarely in forecasting and management studies (e.g., Yoonjae and Barnett 2011; Lim et al 2017; Castaldi 2019; Grid 2019; Shackell and De Vine 2021). Articles like Mossoff’s that problematize or contextualize trademarks are rare in the past decade and usually confined not just to law journals but also to the margins of specialist intellectual property law journals.…”
Section: Trademark Law’s Growing Relevance To Stsmentioning
confidence: 99%
“…A lot of work has been devoted to the design of logistics (supply) chain (Alonso-Ayuso et al, 2003;El Hannach et al, 2016b;Lim et al, 2017;Park et al, 2016;Pisani, 2004). Many researchers consider this problem from an economic point of view.…”
Section: Methodology and Findingsmentioning
confidence: 99%